1999
DOI: 10.1002/(sici)1097-0215(19990531)81:5<820::aid-ijc25>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Sodium selenite-induced oxidative stress and apoptosis in human hepatoma HepG2 cells

Abstract: The mechanisms involved in the anti‐carcinogenic activity of selenium remain to be elucidated. In the present study, we examined sodium selenite‐induced oxidative stress and apoptosis in a human hepatoma cell line (HepG2). Sodium selenite (10 μM) exerted clear cytotoxic effect, as shown by the significant increase of lactate dehydrogenase leakage. Selenite‐induced DNA alterations in apoptosis were studied by: 1. comet assay; 2. TdT‐mediated dUTP nick end‐labeling assay. In addition, characteristic apoptotic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
92
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(105 citation statements)
references
References 19 publications
(19 reference statements)
12
92
1
Order By: Relevance
“…Our results concerning the relation between selenium and apoptosis in humans were contrary to results from several laboratory studies, suggesting that selenium increased anticancer apoptotic activity (34)(35)(36)(37)(38)(39)(40)(41)(42). There are several reasons that our results may differ from laboratory studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results concerning the relation between selenium and apoptosis in humans were contrary to results from several laboratory studies, suggesting that selenium increased anticancer apoptotic activity (34)(35)(36)(37)(38)(39)(40)(41)(42). There are several reasons that our results may differ from laboratory studies.…”
Section: Discussioncontrasting
confidence: 99%
“…The possibility that selenium may increase anticancer apoptotic activity has been suggested by several carcinogenesis studies (34)(35)(36)(37)(38)(39)(40)(41)(42). It is unclear how selenium might induce apoptosis; however, several selenium metabolites, such as hydrogen selenide, methylselenol, and selenodiglutathione, are being researched (43)(44)(45).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that selenium cytotoxicity is related to the generation of free radicals that induces apoptosis (33). However, the selenite concentrations (10 -100 nmol/l) used here to experimentally modulate the GPx activity were within physiological range, and no unwanted side effects of the selenium substitution were observed.…”
Section: Discussionmentioning
confidence: 84%
“…The superoxide anion (O 2 •-) is produced intracellularly by transferring electrons leaked from the electron transport chain in mitochondria and from NADPH cytochrome P450 reductase in the endoplasmic reticulum to oxygen, as well as by the action of several enzymes including NADPH oxidase, lipooxygenase, cyclooxygenase, flavoenzymes (e.g., xanthine oxidase), and uncoupled nitric oxide synthase (47). In particular, the superoxide anion is also formed endogenously by the reaction of selenium compounds such as selenite, selenium dioxide, diselenides, and selenocysteine, and with thiols such as reduced GSH or L-cysteine (3,11,48). The generation of superoxide anions by selenium has been confirmed by treating cells with exogenous GSH or selenite; this has also been observed by adding isolated mitochondria to selenium-containing compounds, including selenite, selenocysteine, selenocystamine, and selenodioxide, to GSH, or to both (10,49,50).…”
Section: Selenium-induced Thiol Oxidation and Ros Generationmentioning
confidence: 99%